The SUbventral-Gland Regulator (SUGR-1) of nematode virulence - Clement Pellegrin; Anika Damm; Alexis L. Sperling; Beth Molloy; Dio S. Shin; Jonathan Long; Paul Brett; Tochukwu Chisom Iguh; Olaf P. Kranse; Andrea Díaz-Tendero Bravo; Sarah Jane Lynch; Beatrice Senatori; et al. (Proceedings of the National Academy of Sciences, 2025)
Pathogens must precisely tailor their gene expression to cause infection. However, a signaling cascade from host signal to effector production has remained elusive for metazoan pathogens. Here, we show that plants contain molecular signals, termed effectostimulins, that activate the first identified regulator of plant-parasitic nematode effectors. SUGR-1 directly binds effector promoters, and is central to a transcriptional network that activates 58 effector genes. Importantly, we demonstrate that downregulation of sugr-1 inhibits parasitism, underlining SUGR-1 signaling as a valuable target for crop protection and food security. This, in the wider context of nematodes as parasites of humans and other animals, has scope for potentially broader impact: Disrupting effector production could, in principle, be applied to any pathogen that secrets effectors.